Asuhan Kebidanan Kehamilan Pada Ny. H Usia 17 Tahun G1P0A0H0 Dengan Anemia Sedang dan KEK Di UPT Puskesmas Sesela Kabupaten Lombok Barat - susilawati, lina; Jarsiah, Jarsiah; Fitriani, Dewi; Mariska, Refina (Journal of Fundus, 2024)
The World Health Organization (2020) noted that the number of cases of anemia in pregnant women reached 43.9% of the total number of pregnant women worldwide, while in Indonesia it reached 84.6% of anemia occurred in pregnant women aged 15-24 years, this increased compared to 2013, which was 37.1%. The purpose of this study was midwifery care for TM III pregnancy in Mrs. H, 17 years old, G1P0A0H1 with moderate anemia and KEK at the Sesela Health Center UPT, West Lombok Regency. The research method used Varney's 7 steps: The results of this midwifery care provide IEC to pregnant women about midwifery care with anemia and KEK. Conclusion Conclusion able to carry out midwifery care for pregnant women with KEK and anemia